2009
DOI: 10.1371/journal.ppat.1000345
|View full text |Cite
|
Sign up to set email alerts
|

Gag Mutations Strongly Contribute to HIV-1 Resistance to Protease Inhibitors in Highly Drug-Experienced Patients besides Compensating for Fitness Loss

Abstract: Human immunodeficiency virus type 1 (HIV-1) resistance to protease inhibitors (PI) results from mutations in the viral protease (PR) that reduce PI binding but also decrease viral replicative capacity (RC). Additional mutations compensating for the RC loss subsequently accumulate within PR and in Gag substrate cleavage sites. We examined the respective contribution of mutations in PR and Gag to PI resistance and RC and their interdependence using a panel of HIV-1 molecular clones carrying different sequences f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
142
3
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(157 citation statements)
references
References 32 publications
11
142
3
1
Order By: Relevance
“…However, efficient processing at the NC-p2 junction to produce mature NC and p2 is required for FIV infectivity. The processing efficiency of the equivalent HIV-1 NC-p1-p6 cleavage junctions has been extensively examined, and proper temporal cleavage at these sites correlates with viral fitness, replication capacity, and drug resistance (11,40,45,47,49,52). The findings of the current study reinforce the notion that the cleavage and maturation of NC-p2 in FIV and of the equivalent NC-p1-p6 in HIV-1 offer a new potential therapeutic target.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, efficient processing at the NC-p2 junction to produce mature NC and p2 is required for FIV infectivity. The processing efficiency of the equivalent HIV-1 NC-p1-p6 cleavage junctions has been extensively examined, and proper temporal cleavage at these sites correlates with viral fitness, replication capacity, and drug resistance (11,40,45,47,49,52). The findings of the current study reinforce the notion that the cleavage and maturation of NC-p2 in FIV and of the equivalent NC-p1-p6 in HIV-1 offer a new potential therapeutic target.…”
Section: Discussionsupporting
confidence: 75%
“…1B). The clinical drugs against HIV-1 PR are very poor inhibitors for wild-type (WT) FIV PR, and interestingly, eight of the drug resistance mutations in HIV-1 PR mentioned above, namely, V11I, K20I, V32I, I50V, I62V, A71I, N88D, and L90M, are already present in the structurally equivalent positions of FIV PR (16 11 I, 25 20 I, 37 32 I, 59 50 V, 71 62 V, 85 71 I, 105 88 D, and 107 90 M [FIV numbering is given, with equivalent HIV-1 numbering in superscript]) (7,24).…”
mentioning
confidence: 99%
“…For 10 patients (5,7,11,13,(15)(16)(17)(18)(19)(20) there were no changes in protease at failure, although nine had baseline protease polymorphisms.…”
Section: Predicted Hla and Kir Immune Escape Mutations In Gagmentioning
confidence: 99%
“…8 Studies have shown that mutations in Gag cleavage sites (CS) also contribute to PI resistance development. [9][10][11][12] HIV-1 PR recognizes and cleaves the Gag and Gag Pol polyproteins to release the structural components: matrix (MA), capsid (CA), p6, nucleocapsid (NC), enzymes protease, reverse transcriptase, RNase H, integrase, the small polypeptides p1 and p2, as well as transframe protein (TFP). 13 Cleavage sites in Gag comprise five amino acids flanking either side of the scissile bond, with position 1 (P1) located immediately upstream and position 1 prime (P1¢) located immediately downstream of the cleavage point.…”
mentioning
confidence: 99%
See 1 more Smart Citation